Trace fossils mistaken as plants: the nomenclatural status of Tetraphyllum (Gesneriaceae) - Bertling, Markus (Phytotaxa, 2019)
Tetraphyllum Griff. ex C.B.Clarke (Gesneriaceae) has erroneously been replaced by Tetraphylloides Doweld, as he considered Tetraphyllum Hosius & von der Marck an angiosperm and thus its earlier homonym. Reinvestigation of the holotype of the type species Tetraphyllum dubium Hosius & von der Marck, however, shows this to be a trace fossil. The latter is re-validated as an ichnotaxon herein. Since botanical and zoological names do not compete for homonymy or synonymy, Tetraphylloides Doweld is a younger synonym of Tetraphyllum C.B.Clarke. In due course, Tetraphylloidinae Doweld is a younger synonym of Tetraphyllinae A. Weber & Mich. Möller; Tetraphylloides Doweld and Tetraphylloidinae Doweld are illegitimate names.